Effects of kinds of additives on fermentation quality, nutrient content, aerobic stability, and microbial community of the mixed silage of king grass and rice straw - Qiu, Chenchen; Yang, Kaili; Diao, Xiaogao; Zhang, Wei; Lv, Renlong; He, Liwen (Frontiers in Microbiology, 2024)
To investigate the effects of kinds of additives on silage quality, the mixture of king grass and rice straw was ensiled with addition of sucrose, citric acid and malic acid at the levels of 0, 1% and 2%, being blank control (CK), citric acid groups (CA1, CA2), malic acid groups (MA1, MA2), citric acid+malic acid groups (CM1, CM2), sucrose groups (SU1, SU2), mainly focusing on fermentation quality, nutrient content, aerobic stability and microbial community of the silages. The results showed that the addition of sucrose decreased (P < 0.05) pH and increased the content of water soluble carbohydrate (P < 0.05). The sucrose groups and mixed acid groups also had a lower (P < 0.01) neutral detergent fiber content. The addition of citric acid and the mixed acid increased (P < 0.01) the aerobic stability of the silage, reduced the abundance of Acinetobacter, and the addition of citric acid also increased the abundance of Lactiplantibacillus. It is inferred that citric acid and malic acid could influence fermentation quality by inhibiting harmful bacteria and improve aerobic stability, while sucrose influenced fermentation quality by by promoting the generation of lactic acid. It is suggested that the application of citric acid, malic acid and sucrose would achieve an improvement effect on fermentation quality of the mixed silage.